Comparative Study of 0.2% Glyceryl Trinitrate Ointment for Pain Reduction after Hemorrhoidectomy Surgery - Vahabi, Sepideh; Beiranvand, Siavash; Karimi, Arash; Moradkhani, Mahmoudreza (The Surgery Journal, 2019)
Context Hemorrhoid is one of the most common diseases in both, men and women, affecting half of the world's population over the age of 50.Aims The aim of this study was to evaluate the analgesic effects of local ointment of glyceryl trinitrate ointment (GTN) after hemorrhoidectomy.Methods and Materials In this randomized double-blind, placebo-controlled study, the patients were grouped as the treatment, that is GTN, and placebo (P) group. After surgery, 0.2% gelatin GTN ointment (250 mg), and P ointment (n = 20 for each group) were applied topically on 1 cm on the anus using a standard ruler, three times a week in respective groups. visual analog scale was used to assess the intensity of the pain and complications of the drugs were observed at 6, 12, 18, and 24 hours.Statistical Analysis Used Data and questionnaires were analyzed statistically using SPSS17 software and results were recorded in the tabular form.Results Six hours after the application of the ointment, no significant difference was found among the groups, however, after 12, 18, and 24 hours significant reduction in pain was seen in GTN group, which was least after 18 hours. The mean values of the total pain score in the first 24 hours after surgery in the GTN group were 3.15 and 5.45 in the P group which were statistically significant. Nonetheless, headache was significantly increased in the GTN group.Conclusion Simple and safe topical GTN ointment can reduce the pain after hemorrhoidectomy, leading to the reduced need of other analgesics.
Keywords: glyceryl trinitrate ointment; hemorrhoidectomy; VAS